(untitled) (Brazilian Journal of Oceanography, 2007)
This study presents data on the reproduction of Abudefduf saxatilis, a rocky shore inhabitant at the northern coast of São Paulo State. A total of 73 individuals were collected using hooks and baits. They were measured, weighed and dissected, sex and maturation stage were analysed, first macroscopically, then part of the material was taken for microscopical confirmation. Visual censuses were also done for underwater observation of egg's presence. Results showed equivalence of males and females in the population, first maturation occurring between 101 and 115mm of total length, spawning period occurs from November to February for Abudefduf saxatilis and October to January for Stegastes variabilis. Reproductive period for A. saxatilis was positively related to air temperature and thermic amplitude, but the environmental clue most likely to influence this rhythm is photoperiod. Transects with visual census of males guarding eggs were also a reliable tool for finding reproductive period in these demersal, egg-guarder species.